Stop the global epidemic of chronic disease ; a practical guide to successful advocacy (WHO GenevaCH, 2007)
Opines that the global epidemic of chronic disease has been widely ignored or seen as less important than other health issues. Suggests that advocacy is essential to help to set the record straight and to spur action at all levels.
Keywords: CHRONIC DISEASES